2011
DOI: 10.1097/inf.0b013e31822d4f56
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Laboratory Values in Patients With Kawasaki Disease

Abstract: BACKGROUND As outlined in the 2004 American Heart Association guidelines, the diagnosis of Kawasaki disease (KD) is supported by results of clinical laboratory studies. However, detailed information regarding the evolution of these results during illness has not been previously reported. The goals of this project were to characterize the evolution of clinical laboratory values in KD before and after treatment with intravenous immunoglobulin (IVIG). METHODS Laboratory values from 380 unselected, consecutive K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 19 publications
10
60
1
3
Order By: Relevance
“…106 Leukocytosis is typical during the acute stage of illness, with a predominance of immature and mature granulocytes. Leukopenia and lymphocyte predominance suggest an alternative diagnosis.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…106 Leukocytosis is typical during the acute stage of illness, with a predominance of immature and mature granulocytes. Leukopenia and lymphocyte predominance suggest an alternative diagnosis.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…18 In addition, patients can present with aneurysms within the first few days after the onset of fever, and two-thirds of patients have a normocytic, normochromic anemia at presentation that is consistent with suppression of erythropoiesis and the anemia of chronic disease. 19 Thus, we must question whether antiinflammatory therapy in KD is always too little, too late. That said, a number of safe, approved therapeutic options for IL-1␤ blockade are currently available.…”
Section: Article See P 1542mentioning
confidence: 99%
“…This is thought to occur as a consequence of the net positive charge of IgG molecule that neutralizes the net negative charge of the red blood cell (RBC) surface (zeta potential), leading enhanced rouleaux formation and accelerated RBC sedimentation. Tremoulet et al stated no difference in comparison of convalescent ESR in IVIG-resistant vs. -subjects responsive to KD; in subjects with aneurysms suggested that the higher ESR was due to more inflammation rather than an effect of a second dose of IVIG (10). It is important to note that both groups of the current study used IVIG; therefore, the effect of IVIG on ESR rise affected both groups.…”
mentioning
confidence: 55%
“…2) No decrease of erythrocyte sedimentation rate (ESR) and/or C-reactive protein (CRP) after one week of treatment (9,10).…”
Section: Methodsmentioning
confidence: 99%